Anthropometry and Metabolic Abnormalities in Obese Children with Non Alcoholic Fatty Liver Disease (East West Medical College Journal, 2025)
Background: Obesity has emerged as a global epidemic in children with a spectrum of psycho-social and medical consequences manifesting across the lifespan. Obesity-related morbidities that emerge early in childhood are an alteration in glucose metabolism and fatty infiltration of the liver. Non-alcoholic fatty liver disease (NAFLD), chronic liver disease is a metabolic complication of obesity. Objective: To identify the prevalence of NAFLD  among obese children and anthropometric and metabolic abnormalities among these obese children  with NAFLD.Methodology: This was a cross sectional study included 50 obese children and adolescents, attending Paediatric Endocrine OPD, BIRDEM from June 2010 to December 2010. BMI e” 95th centile for age and sex was used as an anthropometric marker to diagnose obesity. Obesity with dismorphism, endocrine, chromosomal abnormalities, chronic liver diseases due to infectious or metabolic causes were excluded from the study. Fasting blood samples were collected for measurement of blood glucose, lipid profile, FT4, TSH and SGPT. Fatty liver was diagnosed by USG which includes increased echogenicity of liver, blurring of vascular margins and increased acoustic attenuation.Results: The prevalence of  fatty liver disease among obese children was 36% with male predominance(M72.2%, F 27.8%). Mild NAFLD was 72% followed by moderate 28%.  High Cholesterol, high LDL and high SGPT were more prevalent in obese children with NAFLD which was statistically significant (P